ANALISIS KESALAHAN FONOLOGI DAN SINTAKSIS PADA LATAR BELAKANG SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB - Nisa, Fany Farkhatun (Universitas Muhammadiyah Makassar, 2023)
Language errors are the use of language that deviates from the language rules that apply in a language. Language errors often occur in language learners, including when learning Arabic. These errors can be in the form of verbal or written errors, such as several language errors found by researchers in the thesis of Arabic Language Education Study Program students at IAIN Syekh Nurjati Cirebon. This research aims to analyze Arabic phonological and syntactic errors in the thesis background of students of the IAIN Cirebon Arabic Language Education (PBA) study program for the 2020/2021 academic year. This research is descriptive qualitative research with content analysis methods. The subject of this research is a student's thesis majoring in Arabic Language Education at IAIN Cirebon. The research results show that phonological errors include errors in the use of punctuation marks, errors in reflecting letter sounds, dating of sounds and errors in selecting phonemes in a word. Meanwhile, syntactic errors include: I'rab, Idhafah, Na'at Man'ut errors, adjusting fi'il to Fa'il and errors in Mubtada'.Keywords: Error Analysis, Phonological Errors, Syntax Errors